The Immune Response to Eastern Equine Encephalitis Virus Acquired Through Organ Transplantation - Raabe, Vanessa; Lai, Lilin; Xu, Yong; Huerta, Chris; Wang, Dongli; Pouch, Stephanie M.; Burke, Crystal W.; Piper, Ashley E.; Gardner, Christina L.; Glass, Pamela J.; Mulligan, Mark J. (Frontiers in Microbiology, 2020)
The human immune response to eastern equine encephalitis virus (EEEV) infection is poorly characterized due to the rarity of infection. We examined the humoral and cellular immune response to EEEV acquired from an infected donor via liver transplantation. Both binding and highly neutralizing antibodies to EEEV as well as a robust EEEV-specific IgG memory B cell response were generated. Despite triple-drug immunosuppressive therapy, a virus-specific CD4+ T cell response, predominated by interferon-γ production, was generated. T cell epitopes on the E2 envelope protein were identified by interferon-γ ELISpot. Although these results are from a single person who acquired EEEV by a non-traditional mechanism, to our knowledge this work represents the first analysis of the human cellular immune response to EEEV.